PERANCANGAN SISTEM INFORMASI PENJUALAN TOKO ROTI ME TIME BERBASIS WEB - Agung Aushaaf Marshaa Hermanto; Indra Kanedi; Ricky Zulfiandry (UNIVED Press, 2023)
ABSTRACT: Technological developments mean that from time to time technology continues to develop in a more sophisticated direction. This development is based on human innovation and creativity, especially in the business field, many sales have been made on-line, this Me Time Bakery has not yet developed on-line sales, online developments or online stores through internet media have mushroomed in Indonesia, even already very well known by the general public. The number of various conveniences in shopping and the various types of products and services offered, make Indonesian people make online shops as one of the new